A Comparative Multicenter Study on the Epidemiology of Traumatic Fractures during the Coronavirus Disease 2019 Early Emergency Response Period in Yogyakarta Special Region, Indonesia - Hidayat, Luthfi; Rahayu, Bernadeta Fuad Paramita; Khadafi, Rosyad Nur; Purwanta, Acep Eko Budi; Saputra, Marda Ade; Sumardiyono, Eko; Triangga, Aditya Fuad Robby (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The changes of lifestyle and mobility during the coronavirus disease 2019 (COVID-19) pandemic may influence the epidemiology of traumatic fractures. AIM: This study aimed to investigate the epidemiology of traumatic fractures in Yogyakarta Special Region (Daerah Istimewa Yogyakarta [DIY]) during the COVID-19 emergency response period and compare the data with the similar period in the previous year. METHODS: This was a retrospective study involving five secondary referral hospitals and one tertiary referral hospital. We included all patients who presented to the emergency departments or orthopedic clinics who were then diagnosed with new-onset fractures. We compared the data during the emergency response period (COVID group) with a similar period in 2019 (control group). RESULTS: There were 1249 patients with 1428 fractures included in this study. There was 47.68% reduction of patients during the emergency response period. There was no significant difference in proportion of gender and mean of age (control group vs. COVID group: 55.9% vs. 54.8%, p = 0.717 for male gender; 42.64 ± 24.03 years vs. 42.20 ± 23.34 years, p = 0.886 for mean of patients’ age). There were significant increases in the proportions of patients experiencing low-energy injuries (38.0% vs. 30.8%, p = 0.012), injuries occurring at home (34.0% vs. 23.8%, p = 0.001), and surgically treated closed fractures (51.8% vs. 45.3%, p = 0.038), along with decrease of patients’ referrals (1.6% vs. 4.1%, p = 0.018) during the pandemic. The difference in proportions of fracture type, osteoporotic fractures, and multiple trauma was not significant (control group vs. COVID group: 19.2% vs. 17.4%, p = 0.418 for open fracture; 15.4% vs. 14.7%, p = 0.750 for osteoporotic fracture; and 9.0% vs. 7.0%; p = 0.217 for multiple trauma). CONCLUSIONS: During the COVID-19 emergency response period in DIY, there were nearly half reduction of patients with fractures, increased proportion of patients injured at home, reduced proportion of patients referred to another hospital, and increased proportion of surgically treated closed fractures. The knowledge about this epidemiological trend may help in developing preventive programs and treatment policy for fractures and other injuries during the current pandemic.